Effects Of A Standardized Aqueous Extract Of Polygonum Minus On Stress-Induced Behavior And Neurobiological Changes In Mice - Bashir, Muhammad Irfan (2022)
Stress is a reaction of the body against various physical or emotional events. Stress can induce the depression, anxiety and as well as impairs cognition. Chronic ultra-mild stress (CUMS) model is used to mimic the anxiety and depressive like disorders in animals. There is a need for new medicinal agents to treat the anxiety and mood disorders more adequately. A standardized aqueous extract of Polygonum minus was used in this research, in which quercetin-3- glucuronide and quercitrin (quercetin 3-rhamnoside) were the major constituents. The main aim of this study was to evaluate the effects of P. minus aqueous extract on chronic ultra-mild stress (CUMS) induced behavioral and neurobiological change in mice model. Treatment was given for 8 weeks in which the mice were subjected to chronic ultra-mild stress for 6 weeks. The behavior of subjects was investigated through the sucrose preference test (SPT), forced swimming tests (FST), open field test (OFT), food consumption and food preference tests. Spatial memory was examined through the Barnes maze assay. Furthermore, levels of serum corticosterone, and levels of the following from the brain tissue: brain derived neurotrophic factor (BDNF), serotonin (5-HT), norepinephrine (NE), monoamine oxidase-A (MAO-A) enzyme, Kruppel-like factor 11(KLF11) and sirtuin (SIRT1) were measured.